Teacher readiness to adopt game-based mobile learning with augmented reality - Marques, Margarida M. (2021)
Mobile augmented reality (AR) games have potential in Education, as they can enhance learning experiences, by offering to learners contextualized information. This study aim is to reveal teachers’ readiness to adopt these strategies, after training. Hence, this is a case study of two editions of a workshop under the EduPARK project, designed to support teachers’ adoption of strategies involving game-based mobile learning with AR. The workshops required collaborative exploration of the EduPARK app and educational resource planning. Data collected from individual questionnaires and focus group interviews were analysed through content analysis, descriptive statistics, and computing of the Educational Value Scale and of the System Usability Scale. The 45 teacher-trainees consider they are ready to integrate mobile AR games in their practices, but they are foreseeing difficulties that need to be addressed. This work presents a typology of teacher training that, according to the participants, is successful in promoting their readiness to adopt innovative practices.